Cultivo in vitro e citogenética de Cyrtopodium saintlegerianum Rchb. f.(Orchidaceae: Cyrtopodiinae) - Silva, Daniella Mota (2012)
CyrtopodiumsaintlegerianumRchb. f is an epiphytic species typical of the Midwest, especially in distributed Brazilian Central Plateau, and has a wide geographical distribution in Brazil. It is usually found in the trunks of palm trees, forming large clumps. It has good features for ornamentation, for the beauty and size of its inflorescence, however, are not found in the literature about its conservation, methods for its spread or that could be used in floriculture and landscaping. Thus, this study aimed to establishing protocols for germination asymbiotic effects of phytohormones and acclimatization and characterization of chromosomal species. In 2010, the establishment of micropropagation protocols, capsules were collected in a pasture area in the municipality of Mossâmedes, GO, then the part previously sterilized seeds were separated and tested in a 1% tetrazolium dye.. For cultivation was tested asymbiotic different culture media and then tested after different concentrations and combinations in treatments BAP 16 / ANA, to finally evaluate the acclimatization substrates combined and fertilized with chemical fertilizers and organic. For the karyotype of the species, the plant material is derived from plants grown in vitro in culture medium. We tested four protocols, with differences in enzyme solution for softening the roots, dyes, anti-mitotic concentration of the solution and hydrolysis, and the use of growth regulators for root induction in vitro. All protocols were in common roots pretreated with anti-mitotic 8-hydroxyquinoline (0.002 M) in refrigerator for 24 hours. Then protocols roots were fixed in Carnoy 3:1 for 18 hours the first and second and third and fourth protocol for 24 hours at room temperature. After stored at -20 º C in the same fixative for further analysis (only the fourth protocol). The roots of the protocols were stained with different dyes: hematoxylin, Schiff, acetic orcein and Giemsarespectively.The results of germination was satisfactory in all culture media. For medium supplemented with auxin / cytokinin combined the best concentrations for variable height were 0.2 mg L-1 NAA and BAP without adding control without addition of regulators. The best means to induce large numbers of shoots were 4 mg L-1 BAP and 4 mg L-1 BAP / 0.2 mg L-1 NAA. The number of leaves was rated best in the concentrations of BAP without NAA at concentrations of 1.0, 2.0 and 4.0 mg L-1. The treatments with the highest number of roots were control without added growth regulators at doses of 0.2, 0.5, 1.0 mg L-1 NAA without addition of BAP, as well as the length of roots was favored by the same treatments. The largest number occurred in callus treatment with concentrations of 1.0 mg L-1 BAP without adding ANA. ForcytogeneticsC. saintlegerianum the best protocol was evaluated with the regulator which was obtained metaphases, however chromosomes were condensed, and the number of chromosomes was found to be 2n = 48. cides.